2023
DOI: 10.3390/bios13010109
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Magneto-Plasmonic Nanosensor for Sensitive Detection of Foodborne Pathogens

Abstract: Frequent outbreaks of food-borne pathogens, particularly E. coli O157:H7, continue to impact human health and the agricultural economy tremendously. The required cell count for this pathogenic strain of E. coli O157:H7 is relatively low and hence it is vital to detect at low colony forming unit (CFU) counts. Available detection methods, though sensitive, fall short in terms of timeliness and often require extensive sample processing. To overcome these limitations, we propose a novel magneto-plasmonic nanosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…By means of a combination of fluorescence measurements and magnetic relaxation measurements this method identified different types of food pathogens in industries. Multiparametric magnetofluorescent nanosensors (MfnS) and magneto-plasmonic nanosensor (MPnS) speedily detected pathogenic E. coli O157:H7 (Banerjee et al, 2016(Banerjee et al, , 2017(Banerjee et al, , 2023. Varshney et al (2005Varshney et al ( , 2007 developed magnetic nanoparticle attached antibody conjugates to capture E. coli O157:H7 in ground beef samples.…”
Section: Food Pathogens and Microbial Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…By means of a combination of fluorescence measurements and magnetic relaxation measurements this method identified different types of food pathogens in industries. Multiparametric magnetofluorescent nanosensors (MfnS) and magneto-plasmonic nanosensor (MPnS) speedily detected pathogenic E. coli O157:H7 (Banerjee et al, 2016(Banerjee et al, , 2017(Banerjee et al, , 2023. Varshney et al (2005Varshney et al ( , 2007 developed magnetic nanoparticle attached antibody conjugates to capture E. coli O157:H7 in ground beef samples.…”
Section: Food Pathogens and Microbial Toxinsmentioning
confidence: 99%
“…By means of a combination of fluorescence measurements and magnetic relaxation measurements this method identified different types of food pathogens in industries. Multiparametric magneto‐fluorescent nanosensors (MfnS) and magneto‐plasmonic nanosensor (MPnS) speedily detected pathogenic E. coli O157:H7 (Banerjee et al., 2016, 2017, 2023). Varshney et al.…”
Section: Application Of Nanobiosensors In Food Pathogens and Microbia...mentioning
confidence: 99%
“…Banerjee et al [81] demonstrated the magneto-plasmonic nanosensor (MPnS) by merging spin-spin magnetic relaxation (T2 MR) with SPR characteristics for the monitoring of E. coli O157:H7. N-hydroxy succinimide/1-ethyl-3-[3-(dimethylamino) propyl] carbodiimide hydrochloride (NHS/ EDC) chemistry was used to improve the properties of MPnS with distinct antibodies for the target pathogen on the top of biosensors to identify E. coli O157:H7.…”
Section: Optical-based Systems Relying On Nanomaterials and Polymers ...mentioning
confidence: 99%